RACIAL DIFFERENCES IN MORTALITY RISK IN THE HEALTH, AGING, AND BODY COMPOSITION (HEALTH ABC) STUDY. (30th June 2017) - Marron, M.M.; Ives, D.G.; Bauer, D.C.; Boudreau, R.; Harris, T.; Satterfield, S.; Shorr, R.I.; Newman, A.
Abstract: U.S. blacks have a higher risk of death than whites. This varies by cause of death; stroke, kidney disease and some cancers are higher in blacks. We evaluated cause-specific mortality risk factors in Health ABC to determine whether specific risk factors are more important for these causes of death in blacks than whites. Potential risk factors included: demographics, smoking, body mass index, chronic disease, physical function, and cognition. Among N=3075 participants ages 70–79 (41.7% black), average follow-up was 11.9 years. Underlying cause of death was adjudicated by committee and categorized as: cardiovascular disease, stroke, cancer, dementia, pulmonary, infection, kidney, and other cause. Median survival (95% confidence interval) among black men, white men, black women, and white women was 10.6 (10.0, 11.5), 12.8 (12.4, 13.4), 13.4 (12.6, 14.6), and 15.3 (14.8, 16.2) years, respectively. Adjusting for age and sex, blacks had higher risks of dying from: any cause (hazard ratio=1.32 (1.21, 1.44)), kidney disease (HR=2.10 (1.17, 3.78)), cancer (HR=1.35 (1.13, 1.62)), and stroke (HR=1.32 (0.97, 1.75)). Higher all-cause mortality risk among blacks was attenuated by further adjustment for gait speed (black race adjusted HR=1.06 (0.95, 1.17)) or digit symbol substitution test (black race adjusted HR=1.01 (0.91, 1.12)), but minimally by prevalent diseases (black race adjusted HR=1.25 (1.13, 1.38)). Gait speed also attenuated higher risk of kidney and stroke deaths among blacks, but not cancer deaths. Factors contributing to poorer physical and cognitive function in similarly aged community-dwelling ambulatory black men and women could be targets to reduce disparity and excess mortality.